Analysis and design of the control of level for two interconnected tanks appliying linear matrics inequalities (LMI's) - Rodríguez-Díaz, Oscar Oswaldo; Salamanca, Juan Mauricio (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2006)
The present article describes of didactic form an application of linear matrix inequalities for a system of two tanks interconnected with two variables of the state and one out, whee the exit this given by the height of the level of tank two, aldo it looks for the familiarity of applications with toolbox of LMI´s of Matlab.